Severity of coronary atherosclerosis related to lipoprotein concentration. Issue 6134 (5th August 1978) - Jenkins, P J; Harper, R W; Nestel, P J
Abstract : The influence of individual lipoproteins on the severity of coronary atherosclerosis was studied in 41 patients undergoing coronary angiography. The extent of athero-sclerosis was quantified by a coronary atherosclerosis score (CAS) based on the number and severity of lesions in eight proximal segments of the coronary circulation. The concentration of high-density lipoprotein (HDL) showed a strong inverse association with CAS, which was independent of the effects of age and other lipoproteins. On multivariate analysis concentrations of other lipids–namely, total plasma cholesterol, low-density lipoprotein (LDL) cholesterol, and the combined effect of LDL cholesterol plus very-low-density lipoprotein triglyceride–showed direct, significant correlations with CAS, but these were weaker than that of HDL. This study shows that concentrations of several circulating lipoproteins are related to the severity of coronary atherosclerosis, HDL having an apparent retarding effect. These findings may partly explain the influence of lipoproteins on the development of clinical coronary heart disease.